microRNA-1266-5p directly targets DAB2IP to enhance oncogenicity and metastasis in oral cancer - Chih-Yu Peng; Che-Yi Lin; Szu-Han Chen; Yi-Wen Liao; Cheng-Chia Yu; Shiao-Pieng Lee (Elsevier, 2022)
Background/purpose: Oral cancer has been recognized as one of the most common malignancies worldwide and ranks the fifth leading cause of cancer death in Taiwan. A variety of studies have demonstrated that microRNAs are involved in the regulation of the hallmarks of oral carcinogenesis. Nevertheless, the effect of miR-1266-5p on the tumorigenesis of oral cancer has not been investigated, and not to mention, its functional role in oral cancer. Materials and methods: The upregulation of miR-1266-5p in SASVO3 and SASM5 cells was identified by RNA-Seq and examined by qRT-PCR analysis. The phenotypic assays including proliferation activity, migration capacity, invasion, wound healing, and colony-forming abilities were conducted in oral cancer cells after knockdown of miR-1266-5p. Luciferase reporter and western blotting were used to validate DAB2IP was a direct target of miR-1266-5p in oral cancer. Results: We identified that miR-1266-5p was significantly overexpressed in highly tumorigenic SASVO3 cells and metastatic SASM5 cells. qRT-PCR revealed that miR-1266 significantly increased upregulated in oral cancer and lymph node metastatic tissues compared to normal counterparts We found that downregulation of miR-1266-5p inhibited the proliferation and clonogenicity capacities of SASVO3 cells. Knockdown of miR-1266-5p also inhibited migration/invasion and self-renewal abilities in SASM5 cells. Moreover, we validated miR-1266-5p directly bound to the 3'UTR of DAB2IP in oral cancer cells. We found that DAB2IP knockdown reversed the inhibitory effects of self-renewal and migration mediated by silencing of miR-1266-5p. Conclusion: miR-1266 functions as a biomarker in oral cancer patients, and downregulation of miR-1266 may ameliorate the oncogenic and metastasis potential of oral cancer by targeting DAB2IP.